2021
DOI: 10.3390/rs13224633
|View full text |Cite
|
Sign up to set email alerts
|

Using Daily Nighttime Lights to Monitor Spatiotemporal Patterns of Human Lifestyle under COVID-19: The Case of Saudi Arabia

Abstract: A novel coronavirus, COVID-19, appeared at the beginning of 2020 and within a few months spread worldwide. The COVID-19 pandemic had some of its greatest impacts on social, economic and religious activities. This study focused on the application of daily nighttime light (NTL) data (VNP46A2) to measure the spatiotemporal impact of the COVID-19 pandemic on the human lifestyle in Saudi Arabia at the national, province and governorate levels as well as on selected cities and sites. The results show that NTL bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Despite the differences, a common trend of reduced nightlight during COVID-19 was observed across all major NTL products ( Deep and Gupta, 2021 , Xu et al, 2021 , Alahmadi et al, 2021 , Ghosh et al, 2020 ). Similar to the findings with VNP46A1 in this study, DNB Composites ( Elvidge et al, 2013 ) also showed that radiance decreased significantly from March to May of 2020 relative to the same time frame in 2019 ( Fig.…”
Section: Analysis and Discussionmentioning
confidence: 94%
“…Despite the differences, a common trend of reduced nightlight during COVID-19 was observed across all major NTL products ( Deep and Gupta, 2021 , Xu et al, 2021 , Alahmadi et al, 2021 , Ghosh et al, 2020 ). Similar to the findings with VNP46A1 in this study, DNB Composites ( Elvidge et al, 2013 ) also showed that radiance decreased significantly from March to May of 2020 relative to the same time frame in 2019 ( Fig.…”
Section: Analysis and Discussionmentioning
confidence: 94%
“…Traditional field methods, geographic information systems (GIS), and RS techniques have become increasingly essential due to their ability to provide and analyse historical snapshots of shoreline displacements with higher accuracy [1,2,27]. Utilising satellite imagery and geospatial technology in coastal management and the monitoring of changes in shorelines is significant because of the high-accuracy mapping, reduction in manual errors, synoptic coverage, unbiased results of these approaches, and cost-effectiveness [3,[28][29][30]. Satellite imagery is suitable for mapping and updating shoreline dynamics due to its capability of repetitive coverage, accuracy, and multispectral nature, as well as being a cost-effective tool [4,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…on socioeconomic activity due to their large area coverage and near-real-time acquisition. Studies using NTL data have reported substantial decreases in NTL brightness during the pandemic period in countries such as China [30], India [31] and Saudi Arabia [32]. Xu et al [33] compared the influence of the COVID-19 pandemic in 20 global megacities, using NTL imagery, and found an overall reduction in NTL brightness among the cities of differing magnitudes.…”
Section: Introductionmentioning
confidence: 99%